Réponses

2013-11-20T17:11:50+01:00
Bonjour,

3x(x+1) = 2(1-x)
3x²+3x = 2-2x
3x²+3x+2x-2 = 0
3x²+5x-2 = 0
delta = 5²-4(3)(-2) = 25+24 = 49 = 7²

x_1= \frac{-5+7}{6} = \frac{2}{6} = \frac{1}{3}

x_2= \frac{-5-7}{6}= \frac{-12}{6}=-2

x² = 1-x/6
x²+x/6-1 = 0

delta=( \frac{1}{6} )^2-4(1)(-1)= \frac{1}{36} +4= \frac{1+144}{36} = \frac{145}{36}

x_1= \frac{ \frac{-1}{6} + \frac{ \sqrt{145}}{6} }{2} = \frac{ \sqrt{145} -1}{12}

x_2= \frac{ \frac{-1}{6} -\frac{ \sqrt{145}}{6} }{2} =-\frac{ \sqrt{145} +1}{12}

J'espère que tu as compris
a+